(3EOGQI GdCYeGd GdOhdjI (B/s - (3LhGO, Thbj fGLjs; (3MLGRj, gjKe Ydj s ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2011)
(3GdGYeGd GdOhdjI h eaGgje GdJLGQI, GdHjFI GdGLJeGYjI h GdKbGajI ddGYeGd GdOhdjI, SdWGJ GdMcheI Ydi GdGYeGd GdOhdjI, GdGJaGbjGJ GdOhdjI h efXeGJ GdGYeGd GdOhdjI , GdeNGWQ GdSjGSjI, GdOhd GdfGejI h GdGYeGd GdOhdjI, GdGYeGd h GdGOGQI GdjGHGfjI, GdGbJUGOjGJ PGJ GdJNWjW GdeQcRj, GdJLGQI GdTQbjI `` GdZQHjI, fXGe GdfbO GdOhdj h CShGb QCS GdeGd GdOhdjI, HMhK GdJShjb GdOhdj, JSYjQ h JWhjQ GdSdYI GdOhdjI, GdJhRjY h GdJQhjL GdOhdj, GdeYGedGJ GdJLGQjI GdOhdjI, GdGOGQI GdeGdjI GdOhdjI h GdeMGSHI GdOhdjI, EOGQI GdeYQaI h GdGYeGd GdOhdjI, EOGQI SdSdI GdJhQjO aj GdGYeGd GdOhdjI, Gdgjcd GdJfXjej h GdGSJQGJjLjI h GdJhXja aj GdGYeGd GdOhdjI, fbd GdJcfhdhLjG OhdjG, MGcejI GdTQcGJ h GdCYeGd GdOhdjI, GdSdhc GdGNdGbj h GdGLJeGYj aj GdGYeGd GdOhdjI h CNjQG eSJbHd GdGYeGd GdOhdjIs
(3HHdjhZQGajG(B:(3U(B.417-418s
Keywords: (3EOGQI GdGYeGds; (3GdJShjbs; (3GdJehjd GdOhdjs; (3GdjGHGf(B- (3EOGQI GdCYeGds